Promoting the Participation of Bucha Drum Performing Arts of the Kwan Phayao Community - Tapang, Rattana; Deecharoen, Nutchanart; Khamrong, Nakhon; Dedkaew, Tanapong; Ploykhiew, Ausadawut (Area Based Development Research Journal, 2020)
This participatory research comprised the home, temple and school networks in Bantoon sub-district, Muang district, Phayao province aims to 1) study cultural performing art renovation process, 2) disseminate the knowledge to the youth, and 3) promote participatory network in the community. The research participants included local Bucha Drum performers and patrons, who provided background information. The researchers arranged a community conference to recognize community needs, collaborate in planning, identify the learned lessons, organize the drum rhythm records, record videos, and disseminate the knowledge. To ensure the authenticity regarding the Bucha Drum performance, the Bucha drummer master co-supervised the complete study process. The collaborative project, among the Bantoon sub-district, Bantoon temple, Bantoon sub-district Administrative officer, Fakkawan Wittayakom School, focused on connecting the youth with the local culture within the Bucha drum show. Qualitative data analysis identified directions for performance development and the importance of the Bucha drum for youth development. The follow-up stage considered the Bucha drum performance knowledge transfer and community art promotion, resulting in higher interest for wider community activities. In conclusion, the researching findings and applications enhanced tourism in the Phayao province, community development, and increased youth participation featuring the Bucha drum performance.